Histopathological study of precursor and neoplastic lesions of endometrium in endometrial samplings - Patil, Nanda J.; Shah, Heena P.; Bharti, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Endometrial lesion presenting as abnormal uterine bleeding, abdominal pain and menstrual irregularities form most common presenting complaint in women of reproductive age group and in premenopausal women. Endometrial sampling is a safe and effective diagnostic step in evaluation of abnormal uterine bleeding (AUB). The present study was carried out to establish histopathological diagnosis of precursor and neoplastic lesions of endometrial samplings in correlation with clinical details and other investigations. Methods: A two-year prospective study was carried out in the department of pathology in a tertiary care hospital from June 2013-May 2015 which included endometrial samplings of precursor and neoplastic lesions. All cases were analyzed histopathologically. Results: The study included 46 cases comprising 30% of total 153 endometrial samplings. Out of these, precursor lesions were 36 cases (23.6%) and malignant were 10 case (5.8%). The highest incidence of precursor lesions (endometrial hyperplasia) was in the age group of 41- 50 years. Among the precursor lesions, endometrial hyperplasia without atypia (86%) was the commonest observation followed by atypical hyperplasia (14%). Conclusions: For the correct evaluation of cases presenting with AUB, histopathological evaluation of endometrial samplings is the gold standard method.